POSSIBILITIES OF USING DIALECT ATLASES IN THE ACQUISITION OF LATVIAN LANGUAGE - Vulāne, Anna; Stikute, Elita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The creation of a modern lesson increasingly uses open data, a variety of digital resources, electronic teaching tools etc. In addition to books, electronic teaching tools, information resources, etc., come into the training process as a way to portray linguistic information and the writers' creative thought. One of the resources that can be successfully exploited in promoting the growth of a fully developed and skilled pupil, as well as in-depth learning of the Latvian language, is dialect atlases. The aim of the research was to understand the functionality and effectiveness of the dialect atlases in lear ning lexicology and dialectology. The study combined the descriptive method and content analysis, and was conducted with the help of experiments and questionnaires.The article describes the experience gained through the use of the „Atlas of the Latvian Dialects” in learning Latvian. It characterises the use of maps within the „Lexicon” part of the Atlas to develop pupils' socio-cultural competence, to enhance text composition, analytical, digital and self-guided learning skills and it outlines the role of phonetics and morphology parts of the Atlas in the development of pupils' linguistic competence.